PENDALAMAN MATERI AKUNTANSI UNTUK E-COMMERCE BAGI SISWA/I SMA RICCI - Wijoyo, Amin; Nicholas Richardson; Cherry Tanichi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2024)
Education about accounting for e-commerce for students at RICCI Senior High School is Community Service activities which involve the participation of professors and students from Tarumanagara University which aim to having a positive impact on the educational in Indonesia. This program contributes by providing additional knowledge about accounting records for e-commerce and all related transactions within an accounting period. The comprehensive program was held RICCI Senior High School on March 7 2024, and was attended by 20 RICCI Senior High School students. The significance of this program lies in its two main impacts of providing practical insight into accounting for e-commerce and give the students' general explanation of accounting principles. This activity involves a theoretical discussion regarding basic accounting concepts, accounts related to accounting records for e-commerce, an explanation of how to make a profit and loss report, and practical exercises to facilitate students' understanding of the material being taught. It is hoped that the learning of this material can prepare RICCI Senior High School students to make them understand about accounting for e-commerce and make it easier for them to the higher education and the world of work in the future. As a measure of success, at the end of the community service activity, an impresive of 75% of RICCI High School students managed to answer correctly the question bank on Kahoot, that proved that they understood accounting for e-commerce. These results provide evidence of the program's effectiveness in encouraging the achievement of substantial learning outcomes among participating students. ABSTRAK Pendalaman materi akuntansi untuk e-commerce bagi siswa-siswi di SMA RICCI merupakan kegiatan Pengabdian Kepada Masyarakat (PKM) yang melibatkan adanya partisipasi oleh para dosen dan mahasiswa-mahasiswi dari Universitas Tarumanagara yang bertujuan untuk memberikan dampak positif pada pendidikan di Indonesia. Program ini memberikan kontribusi dengan menyediakan pengetahuan tambahan tentang pencatatan akuntansi untuk e-commerce dan segala transaksi yang terkait dalam periode akuntansi. Penyampaian materi mengenai akuntansi untuk e-commerce dilakukan secara langsung di SMA RICCI pada tanggal 7 maret 2024, dan diikuti oleh 20 siswa/i SMA RICCI. Signifikansi dari kegiatan ini terletak pada dua dampak utamanya, yaitu memberikan wawasan praktis tentang akuntansi untuk e-commerce dan memperluas pemahaman umum siswa tentang prinsip akuntansi. Kegiatan ini melibatkan diskusi teoritis mengenai konsep akuntansi dasar, akun-akun yang terkait dalam pencatatan akuntansi untuk e-commerce, penjelasan mengenai cara untuk membuat laporan laba rugi, dan latihan praktik untuk dapat mempermudah pemahaman siswa-siswi terhadap materi yang diajarkan. Penguatan pemahaman terhadap materi ini diharapkan dapat mempersiapkan siswa/i SMA RICCI menghadapi tuntutan pendidikan tinggi dan dunia kerja di masa depan. Sebagai ukuran keberhasilan, pada akhir kegiatan PKM, sebanyak 75% siswa SMA RICCI berhasil menjawab dengan benar bank soal di Kahoot, mencerminkan bahwa mereka telah paham mengenai akuntansi untuk e-commerce. Hasil ini menjadi bukti keefektifan program dalam mendorong pencapaian hasil belajar yang substansial di kalangan siswa yang berpartisipasi.